Sejarah dan Dampak Misi Kristen di Kampung Besiq, Kutai Barat Tahun 1966 - Agnesia Pauline; Demsy B. Salindeho; Jamil Jamil (Yupa: Historical Studies Journal, 2021)
The existence of the Dutch ruling in Indonesia brought the development of Protestant Christianity. Continued with the entry of zending who came with the spirit of Pietism (pious people who practice God's word) which in principle prioritizes repentance, teaching faith experiences in daily life and in worship. They were sent to carry out the mission of preaching the gospel to all mankind who do not yet believe in the Lord Jesus Christ. In West Kutai, Christianity is also growing rapidly as evidenced by the existence of the majority of people who embrace Protestant Christianity. One of them is Besiq village, which is located in the interior of West Kutai, Christianity has also developed in this village where the majority of the people embrace Protestant Christiani